The effect of multilingual suggested tags on cross-language information tagging behaviour. Issue 2 (8th June 2021) - Ma, Xiaoyue; Zhang, Siya; Zhao, Pengwei
Abstract : Purpose: Suggested tag was considered as one of the critical factors affecting a user's tagging behaviour. However, compared to the findings on the suggested tags for the monolingual environment, it still lacks focused studies on the tag suggestions for cross-language information. Therefore, this paper aims to concern with annotation behaviour and psychological cognition in the cross-language environment when suggested tags are provided. Design/methodology/approach: A cross-language tagging experiment was conducted to explore the impact of suggested tags on the tagging results and process. The descriptive statistics of tags, the sources and semantic relations of tags, as well as the user's psychological cognition were all measured in the test. Findings: The experimental results demonstrated that the multilingual suggested tags could bring some costs to a user's tagging perception. Furthermore, the language factor of suggested tags led to different paths of tagging imitation (reflected by longer semantic mapping and imitation at the visual level) and different cognitive processes (topic extraction and inference process). Originality/value: To the best of the authors' knowledge, this study is one of the first to emphasize the effect of suggested tags during multilingual tagging. The findings will enrich the theories of user-information interaction in the cross-language environment and, in turn, provide practical implications for tag-based information system design.